PENGARUH EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP PERTUMBUHAN Salmonella typhi - Saputera, Syadzli Agus; Fifendy, Mades; Fitriani, Vivi (STKIP PGRI Sumbar, 2013)
ABSTRACTSalmonella typhi is the bacterium that causes fever typhoid. Typhoid fever is still an endemic disease in Indonesia. Typhoid occur in the presence of bacterial infection Salmonella typhi. Combating bacterial infection can be done by giving antibiotics, but bacteria have a high level of resistance to antibiotics. Bacterial resistance to antibiotics caused an increased mortality rate. It is therefore necessary to find a new alternative antimicrobial drugs. Binahong (Anredera cordifolia (Ten.) Steenis) is a plant that has a role as antimicrobial compounds that contain antimicrobials such as flavonoids, alkaloids, terpenoids and saponins. The purpose of this study was to determine the effect of leaf extract binahong (Anredera cordifolia (Ten.) Steenis) on the growth of Salmonella typhi bacteria. The experiment was conducted from August to September 2013 in the Laboratory Kopertis X, Padang. Using a completely randomized design (CRD) with 6 treatments and 3 replications. Data were analyzed by analysis of variance (ANOVA), and a further test of Least Significant Difference (LSD). The results showed each treatment binahong leaf extract (Anredera cordifolia (Ten.) Steenis) provide inhibition to the growth of Salmonella typhi. From the study concluded binahong leaf extract (Anredera cordifolia (Ten.) Steenis) can inhibit the growth of Salmonella typhi.Â